(Queer)-ying in South African secondary schools: narratives of queer teachers and what they reflect on gender and sexuality discourse in post-apartheid South Africa - Mustafa, Sumanah (My University, 2021)
Queer teachers’ positionalities reveal the relationship between identity (the personal), navigations around power (the political) and their teaching and learning practices (the pedagogical). This research focused on how queer teachers in South African secondary schools navigate the complexities of their identities in terms of their own in(visibility) within schooling spaces that have been historically (and presently) heteronormative, militarised and masculine. Moreover, this research was concerned with whether queer teachers resist and/or co-opt modes of surveillance within South African secondary schools. This research drew from qualitative data from six in-depth, one-on-one, semi-structured interviews with queer teachers that have worked in a range of South African secondary schools. This research used thematic network analysis to situate themes within greater discourse around gender and sexuality in post-Apartheid South Africa, in order to reveal the interplay between how queer teachers navigate and make sense of their identities within existing power structures. The analysis indicated that there are multiple complexities that queer teachers face when navigating their identities. Issues of private/public identities, feelings of safety, precarious places of pedagogy and dominant modes of surveillance were revealed to be factors that heavily influence queer teachers’ everyday experiences and teaching practices. Therefore, queer teachers in South African secondary schools negotiate their (in) visibility based on whether they feel safe and supported to do so. Furthermore, this research revealed that many modes of surveillance remain historical which in turn create contextual barriers for queer teachers to express themselves. These barriers are largely a result of South African secondary schools co-opting disciplinary practices (both materially and symbolically) which are homophobic, patriarchal and colonial. However, this research revealed that despite many modes of surveillance, queer teachers found ways to resist both personally and pedagogically. Lastly, this research reflects on whether queer teachers have a duty to disrupt the norms in schools when they can be systemically pressured to co-opt modes of discipline and surveillance for everyday survival
A research report submitted in partial fulfilment of the requirements for the degree Master of Arts in Critical Diversity Studies to the Faculty of Humanities, School of Social Sciences, University of the Witwatersrand, 2021